1982
DOI: 10.1136/adc.57.4.287
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal function after combination chemotherapy for Hodgkin's disease in childhood.

Abstract: SUMMARY The effect of quadruple chemotherapy (mustine, vincristine, procarbazine, and prednisolone) on gonadal function was investigated in 15 males and 2 females treated for Hodgkin's disease during childhood. The 2 females have regular menstrual cycles with evidence of ovulation in one. Twelve of the males have shown normal progression of pubertal development since completing their treatment. Nine out of 10 late pubertal or adult subjects had small testes but only one developed gynaecomastia. All 4 prepubert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
2

Year Published

1984
1984
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 14 publications
0
35
1
2
Order By: Relevance
“…A number of previous studies have reported on reproductive function following treatment for Hodgkin's disease in childhood with MOPP (Whitehead et al, 1982b;Ortin et al, 1990) and OPPA/COPP (Bramswig et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have reported on reproductive function following treatment for Hodgkin's disease in childhood with MOPP (Whitehead et al, 1982b;Ortin et al, 1990) and OPPA/COPP (Bramswig et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Infertility appears to be almost inevitable in adult males with Hodgkin's disease treated by six or more courses of MOPP or MVPP (mustine, vincristine/vinblastine, procarbazine, prednisolone) (Whitehead et al, 1982a). Chemotherapy induced testicular damage in patients treated for Hodgkin's disease in childhood was first reported by Sherins et al, in 1978. Whitehead et al (1982b reported 15 males treated with MOPP for Hodgkin's disease in childhood and concluded that severe testicular damage is common, with azoospermia, but normal pubertal development.…”
mentioning
confidence: 99%
“…16,17 Ovarian damage is Original Article drug and dose dependent and is related to the patient's age at time of treatment, with progressively smaller doses required to produce ovarian failure with increasing age. 18 It is important to emphasize that there is no evidence that the prepubertal ovary is protected from chemotherapy or radiotherapy.…”
Section: Cancer Treatment and Ovarian Functionmentioning
confidence: 99%
“…In one study of long-term survivors of childhood cancer, 6 of 13 patients treated prepubertally had a normal or near-normal reproductive state compared to 7 of 14 treated postpubertally (129). Interestingly, tests to detect abnormal testicular function, such as basal levels of gonadotropins and gonadotropin response to GnRH, are unlikely to detect testicular damage in prepubertal boys (130). This is illustrated by the case of a 6-year-old boy who received chemotherapy and had normal FSH levels prepubertally but then had abnormally high levels of FSH in early puberty (130).…”
Section: Prenatal Exposuresmentioning
confidence: 99%
“…Interestingly, tests to detect abnormal testicular function, such as basal levels of gonadotropins and gonadotropin response to GnRH, are unlikely to detect testicular damage in prepubertal boys (130). This is illustrated by the case of a 6-year-old boy who received chemotherapy and had normal FSH levels prepubertally but then had abnormally high levels of FSH in early puberty (130). Leydig cell function is generally not affected by chemotherapy in the prepubertal male, as assessed by mean baseline and GnRH-stimulated LH levels and onset of puberty (131).…”
Section: Prenatal Exposuresmentioning
confidence: 99%